Conversations in development: Jimmy Smith part I - Smith, Jimmy W. (Burness Communications, 2013)
Ellen Wilson interviews Jimmy Smith, director general of the International Livestock Research Institute (ILRI), on his inspiration and livestock's critical role in development.